Matrix Approach to Analysis of Human Errors and their Prevention by Quality Engineering and Managerial Tools. (16th March 2015) - Bashkansky, Emil; Dror, Shuki
Abstract : We apply well‐known quality engineering matrix techniques such as quality function deployment; Teoriya Resheniya Izobretatelskikh Zadatch (TRIZ); and failure mode, effects, and criticality analysis for characterizing, mapping, and preventing human error (or, at least, reducing damage caused by errors). Human errors ('WHATs', in the language of quality function deployment) are classified according to 10 characteristics, while 20 typical types (or protective layers)—'HOWs'—in quality assurance systems are proposed for preventing/stopping/minimizing to some extent damage caused by the error. During the analysis of a specific system, any error is estimated according to its likelihood and severity, and every protective layer receives a score according to its effectiveness in preventing errors. Synergy or antagonism between protective layers may also be taken into account when calculating the effectiveness. The approach facilitates evaluation and comparison of the effectiveness of different quality assurance systems dealing with human errors. The authors emphasize the need to create a 'recipe book' based on a historical database, which will enable, after characterizing the potential human errors according to the 10 criteria mentioned earlier, application of the optimal prevention efforts. The proposed approach is illustrated by an example of product delivery errors analysis. Copyright © 2015 John Wiley & Sons, Ltd.